Recent Advances in Information and Communication Technology 2016 Proceedings of the 12th International Conference on Computing and Information Technology (IC2IT) - Meesad, Phayung; Boonkrong, Sirapat; Unger, Herwig (Advances in Intelligent Systems and Computing, 2016)
This proceedings book presents recent research work and results in the area of communication and information technologies. The chapters of this book contain the main, well-selected and reviewed contributions of scientists who met at the 12thInternational Conference on Computing and Information Technology (IC2IT) held during 7th - 8th July 2016 in Khon Kaen, Thailand The book is divided into three parts: "User Centric Data Mining and Text Processing", "Data Mining Algoritms and their Applications" and "Optimization of Complex Networks".